Favorite TV Channels / as News Sources for Iraqi University Professors. - Al-Hiti, Hafez Yassin (ALBAHITH ALALAMI, 2015)
The growing ability of Television to transfer and present events as they occur and sometimes transfer events alive makes it the most important sources to receive news and find out what is going on in the world. These channels form the importance of multiple sources and displayed content, especially news. What adds to the importance of the research is that the people under study are Iraqi professorsThe problem of the study is represented by an essential inquiry about the favorite satellite channels to obtain news for Iraqi professorsThe aims of the study are identified by finding out the most favorite satellite channels as a source of news for Iraqi professors and the habits of exposer to the news by them The research is a descriptive study depending on the survey method to analyze the event under study. The researcher uses the questionnaire as a basic tool for gathering information. She/he distributed 360 questionnaires on chosen professors at three universities (Al-Anbbar University, Al-Mustansiriya University, and Babyl University)The most important results are as follows: al-Iraqia, al-Sharqiya, al-Arabiya, Al-Jazeera, and al-Arabiya al-hadath get the first five mattresses as a source of news for male Iraqi professors, and al-Sharqiya, al-Arabiya, al-Iraqia, al-Jazeera, and al-Arabiya al-hadath get the first five mattresses as a source of news for female Iraqi professors